Vine cultivation and wine production in Ribeiro de Avión: a historical and geographical approach (Revista Española de Estudios Agrosociales y Pesqueros, 2023)
Knowing the magnitude and scope of wine production, and identifying the most significant lands and localities that for years have been dedicated to the cultivation of the vine in the Orense municipality of Avión (integrated in the Ribeiro region) are the priority objectives of this research. The work is structured into four fundamental sections: the first analyzes the production of wine by plane during the 18th and 19th centuries, the second deals with the cultural landscapes generated by the cultivation of the vine between 1944 and 1960, and the third the situation in which the vineyards are found at the beginning of the 21st century is evaluated and the last section delves into the archaeological heritage derived from the wine-growing activity. The study carried out shows that the vineyard in Avión has been very present for almost 300 years, at least in 44 % of its parishes. In this sense, the wineries that operated in the towns of Beresmo, Amiudal and Mourelle played a very active role, which together came to have, in 1944, a cultivated graphic area that exceeded 112.51 hectares dedicated to the care and exploitation of the vine, resulting in a considerable annual production of almost 2,445 hectoliters of wine.
Keywords: cultivation of the vine; ribeiro region; avión; cultural landscapes; land abandonment